Enhancing procedural equity in judicial decision-making within neutrosophic contexts - Edwin Bolívar Prado Calderón; Cecilia Campaign Muñoz Leny; Salomón Alejandro Montece Giler; Leonso Dagoberto Torres Torres (Journal of Fuzzy Extension and Applications)
This study introduces a neutrosophic Multi-Criteria Decision-Making (MCDM) framework to evaluate judicial resources in protection actions within the province of Pichincha, Ecuador, with a focus on enhancing procedural equity. By integrating the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) with Ordered Weighted Averaging (OWA) within a neutrosophic context, the proposed approach addresses the inherent ambiguity and uncertainty of judicial processes. The neutrosophic framework enables a comprehensive assessment of judicial resources by incorporating degrees of truth, indeterminacy, and falsity in evaluations, offering a robust alternative to traditional MCDM methods that often struggle with subjectivity and ambiguity in legal settings. Key findings indicate that requests for review of judgments and pre-trial consultations are the most effective resources for ensuring procedural fairness and equity in judicial outcomes. This study underscores the potential of neutrosophic methods to optimize decision-making processes in the judicial field, facilitating a more transparent, objective, and equitable approach to resource evaluation. These findings open avenues for further research on the application of neutrosophic MCDM methods in legal systems and other domains where uncertainty significantly impacts decision quality.